Ultrasound-assisted extraction of peanut shell by-product: Chemical properties, antioxidant, and anti-inflammatory effects - Kang Jung Wook; Lee In Chul (Archives of Biological Sciences)
Peanut shell by-products have been explored for their pharmacological potential, particularly through applications developed from their utilization. This study aimed to investigate the effects of peanut shell extract (UPE) obtained via ultrasound-assisted extraction (UAE) on lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. High-performance liquid chromatography analysis revealed elevated levels of luteolin in the ultrasound-extracted peanut shell extract (UPE). UPE demonstrated significant in vitro antioxidant activity, as evidenced by its ability to scavenge 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2'-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radicals. The anti-inflammatory effects of UPE were assessed using the nitric oxide (NO) Griess assay, prostaglandin E2 (PGE2), and interleukin-6 (IL-6) enzyme-linked immunosorbent assay (ELISA). Western blot analysis and reverse transcription polymerase chain reaction (RT-PCR) were used to evaluate the expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). UPE significantly reduced NO, PGE2, and IL-6 levels in LPS-treated RAW 264.7 cells, suggesting potent anti-inflammatory properties. Furthermore, UPE downregulated the expression of iNOS and COX-2, thereby suppressing NO and PGE2 production. These findings indicate that peanut shell extracts obtained through UAE have therapeutic potential due to their enhanced antioxidant and anti-inflammatory effects, likely attributed to increased levels of luteolin.